A hemicyanine-based fluorescence probe for selective detection of CYP2D6 in living cells and tumor-bearing mice. (February 2022) - Xu, Siquan; Xing, Xinyi; Liu, Yongyi; Gao, Hui
Abstract: Cytochrome P450 (CYP) 2D6, as the only active CYP2D subfamily enzyme in humans, involved in metabolizing 25% of clinical drugs, including antidepressants, antiarrhythmic drugs, antipsychotics and analgesics. Herein, two novel enzyme-activatable fluorescent probes (McMe and BnMcMe ) were constructed and synthesized to monitor the activity of CytochromeP4502D6 (CYP2D6) in complex biological systems. McMe possessed excellent selectivity and sensitivity in response to CYP2D6 enzyme with 9-fold fluorescence changes and the limit of detection (LOD) = 0.052 nM. The fruitful application of McMe in living cells and tumor-bearing mice implied that it can be used to measure the activity of endogenous CYP2D6 . These researches indicated that McMe could be served as an effective molecular tool to specifically bio-image the activity of endogenous CYP2D6 in nude mice, which may provide assistance to investigate the function of CYP2D6 in drug metabolism and pathologic process. Graphical abstract: Image 1 Highlights: Selective detection of CYP2D6 with obvious color change and turn-on fluorescence signal. Detection limit of CYP2D6 was found to be 0.052 nM. Visual detection of CYP2D6 in human liver microsomes (HLMs), living cells and tumor-bearing BALB/c nude mice. Excellent fluorescence imaging and biological imaging performance attributed to ICT effect.